South east villages in the province of Buenos Aires, an approach to the study of its population dynamics (Huellas, 2019)
The meaning and function of small villages in the south east of the province of Buenos Aires has shifted throughout time. Traditionally, a high proportion of minor urban centers grounded on the fact that communications were highly difficult and agricultural spaces needed to be placed near towns for their supply and for the marketing of their products. Currently, the role of many of the so-called minor towns has changed, together with their ability to remain in place or not, to provide services to the agricultural sector, or to take a new direction towards tourism. Accordingly, though in an incipient way, certain smaller localities are undergoing changes that are characterized by the restructuring of the productive processes that arose in the rural areas surrounding them, by the increase in non-agricultural activities or by the intensification of urban-rural flows. In this sense, this paper aims at analyzing the dynamics of the population residing in towns in the south east of the province of Buenos Aires, especially small towns, along the latest inter-census periods, trying to identify certain characteristic features of ruptures and continuities within spatial and temporal levels.
Keywords: Minor localities; population dynamics; southeastern province of Buenos Aires